Population pharmacokinetic modeling of ilaprazole in healthy subjects and patients with duodenal ulcer in China - Yu, Mengyang; Liu, Shupeng; Wu, Xiaofei; Wang, Hongyun (Frontiers in Pharmacology, 2024)
Aims: This study aimed to develop a population pharmacokinetic (PopPK) model of ilaprazole in healthy subjects and patients with duodenal ulcer in Chinese and investigate the effect of potential covariates on pharmacokinetic (PK) parameters.Methods: Pharmacokinetic data from 4 phase I clinical trials and 1 phase IIa clinical trial of ilaprazole were included in PopPK analysis. Phoenix NLME 8.3 was used to establish a PopPK model and quantify the effects of covariate, such as demographic data, biochemical indicators and disease state on the PK parameters of ilaprazole. The final model was evaluated by goodness-of-fit plots, bootstrap analysis, and visual predictive check.A two-compartment model with first-order elimination successfully described the pharmacokinetic properties of ilaprazole. In the final PopPK model, body weight and sex were identified as statistically significant covariates for volume of peripheral compartment (Vp) and clearance of central compartment (CL), respectively, and disease status was also screened as a significant covariate affecting both CL and Vp. The validation results demonstrated the good predictability of the model, which was accurate and reliable.Conclusions: This is the first population pharmacokinetics study of ilaprazole in the Chinese, and the PopPK model developed in this study is expected to be helpful in providing relevant PK parameters and covariates information for further studies of ilaprazole.